Optimization of the osmotic dehydration process for improving the quality of vacuum-fried Vinh Chau shallots at the pilot stage [pdf] - Ngo Van Tai; Nguyen Minh Thuy (My University, 2023)
In recent years, particularly during the Covid-19 pandemic, food with high biological activities, which might help to enhance the immune system and reduce the risk of disorders, has attracted public attention (Bellavite and Donzelli, 2020).The onion (Allium ascalonicum) is one such plant with high antioxidant compounds, including phenolics, flavonoids, kaempferols, and quercetin (Thuy et al., 2020).These compounds have health benefits, such as preventing cancer, anti-microbiological activities, strengthening cardiovascular health, reducing high blood pressure and insulin resistance, controlling weight, antioxidant activity, and fighting chronic bronchitis, infections, and fever (Donno et al., 2019;Paczkowska-Walendowska et al., 2021).However, in Vietnam, the shallot is not used effectively, and the price of these materials
Keywords: Osmotic dehydration; Osmosis; Garlic and Onion Studies